A cup o’ controversy: coffee and health in 19th century Rio de Janeiro - Couto, Cristiana Loureiro de Mendonça; Alfonso-Goldfarb, Ana M. (Circumscribere International Journal for the History of Science, 2016)
Due to the local favorable climate and soil, availability of slave manpower and technical simplicity, the coffee exports soon surpassed the one of the traditional Brazilian crops. By mid-19th century, Brazil had become the first world coffee producer, which fact had a major role in the early development of industry in the country. Given such high status and increasing consumption by the local population, coffee also awakened the interest of the Brazilian doctors, as reflected in the theses defended at the School of Medicine of Rio de Janeiro between 1850 and 1880. In the present article we analyze the perceptions of Brazilian doctors on the properties of coffee, mainly its power as a nutrient and use for the treatment of diseases. Coffee also earned a place in the contemporary books of etiquette and cookbooks published in Brazil and abroad, as we address briefly. In either case, coffee represents a valuable element for the understanding of the relationship between nutrition and health in 19th-century Brazil.